2022
DOI: 10.1007/s11695-022-06404-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sleeve Volume Between Banded and Non-banded Sleeve Gastrectomy: Midterm Effect on Weight and Food Tolerance—a Retrospective Study

Abstract: Background Sleeve dilatation after laparoscopic sleeve gastrectomy (LSG) causes weight regain (WR). Banded sleeve gastrectomy (BSG) was proposed to prevent dilatation and reduce WR. Methods A retrospective cohort study on patients who underwent BSG and LSG and completed 4 years of follow-up from 2016 to 2021 was included. Body mass index (BMI), percentage of excess weight loss (%EWL), percentage of total weight loss (%TWL), and FT scores were calculated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…2) After 12 months, seven studies, including 1,962 patients, reported this outcome with substantially greater EWL for the LBSG group with 3.30 [0.42, 6.18], the p-value was 0.02. 3) EWL was reported after 24 months of follow-up in six studies encompassing 2,007 patients [17,18,20,[22][23][24]. our analysis showed substantially higher %EWL in the LBSG group than the other group (MD=4.13; 95%CI = [1.44, 6.81]; p-value of 0.003).…”
Section: Figure 3: Forest Plot Of Bmi Figure 4: Forest Plot Of Bmi (A...mentioning
confidence: 51%
See 2 more Smart Citations
“…2) After 12 months, seven studies, including 1,962 patients, reported this outcome with substantially greater EWL for the LBSG group with 3.30 [0.42, 6.18], the p-value was 0.02. 3) EWL was reported after 24 months of follow-up in six studies encompassing 2,007 patients [17,18,20,[22][23][24]. our analysis showed substantially higher %EWL in the LBSG group than the other group (MD=4.13; 95%CI = [1.44, 6.81]; p-value of 0.003).…”
Section: Figure 3: Forest Plot Of Bmi Figure 4: Forest Plot Of Bmi (A...mentioning
confidence: 51%
“…We applied our inclusion and exclusion criteria, resulting in 29 articles available for full-text examination. Finally, we had 15 studies [10,[17][18][19][20][21][22][23][24][25][26][27][28][29][30] included in this systematic review meta-analysis. The PRISMA diagram depicting this selection process is shown in Figure 1.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our study, patients had a four-fold stomach volume, which might have contributed to the weight regain since more dilation is correlated to less restriction and, therefore, more food consumption. A study by Hany et al found that in a retrospective trial with four years of follow-up after primary LSG with or without a ring, that banded LSG had significantly lower sleeve volume, significantly lower WR, and significantly lower FT scores than LSG and that the ring can work as a possible prevention against stomach enlargement [ 27 ].…”
Section: Discussionmentioning
confidence: 99%